Changes in the Meaning of Space Around the Lematang River in the 1910 - 1980s - Dennys Pradita; Ari Mukti Wardoyo Adi; Devi Itawan; J. Susetyo Edy Yuwono (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2024)
Abstract: The ideas brought by the externals had major implications. The idea of natural exploitation as well as economic advancement around the Lematang River occurred from the beginning of the 20th century to the first half of the 20th century, which had a major impact on the community. The communities around the Lematang River were originally settled and dependent on the river life. This study aims to examine the changes in the meaning of space due to changes in the natural landscape. This research uses the historical method. The results showed that exploitation around the Lematang river flow intensified in the early 20th century through plantations, trade and mining. Similar conditions also existed during the New Order period, the government tried to accelerate the economic progress of the region by opening roads and bridges which further changed the meaning of the community regarding the river. Changes in the natural landscape due to the existence of plantations and also land routes have become a magnet for people to move to become farming communities or planters who do a lot of activities on land and there are changes in the concept of space around. Abstrak: Gagasan mengenai ekploitasi alam dan juga kemajuan ekonomi di sekitar aliran sungai Lematang terjadi dari awal abad XX sampai paruh pertama abad XX yang berdampak besar terhadap masyarakat. Masyarakat di sekitar aliran sungai Lematang pada mulanya menetap dan bergantung pada kehidupan sungainya. Penelitian ini bertujuan untuk mengkaji mengenai perubahan pemaknaan ruang akibat adanya perubahan lanskap alam. Penelitian ini menggunakan metode sejarah. Hasil penelitian menunjukkan eksploitasi di sekitar aliran sungai Lematang semakin gencar pada awal Abad XX melalui perkebunan, perdagangan dan juga pertambangan. Kondisi serupa juga terjada pada masa Orde Baru, pemerintah berupaya mempercepat kemajuan ekonomi Kawasan dengan membuka jalan dan jembatan yang semakin mengubah pemaknaan masyarakat mengenai aliran sungai. Perubahan lanskap alam akibat adanya perkebunan dan juga jalur darat telah menjadi magnet bagi masyarkat untuk berpindah menjadi Masyarakat petani atau pekebun yang banyak beraktifitas di daratan serta ada perubahan mengenai konsep ruang di sekitar.